Elucidation study of bioavailable potential among plant-based silver nanoparticles fabricated from several local fruit peels / Zainab Razali ... [et al.] - Razali, Zainab; Jami’an, Nur Syahzanani Aqilah; Jaafar Sidik, Norrizah; Md Kawi, Roejhan (Penerbit UiTM (UiTM Press), 2025)
Plant-based silver nanoparticles (AgNPs) derived from biological waste (fruits) have piqued researchers' interest due to their remarkable antibacterial and antioxidant characteristics, as well as toxicity studies. This study aimed to elucidate the bioavailable potential of AgNPs from silver nitrate fabricated from A. comosus, G. mangostana, and M. indica peel extracts as green reducing agents. UV-Vis and FTIR analysis corroborated the presence of AgNPs. Antibacterial activity against S. aureus and E. coli was evaluated using the disc diffusion and minimum inhibitory concentration (MIC) techniques. Interestingly, all peel extracts successfully produced AgNPs, resulting in reddish-dark brown alterations with a peak absorbance at 432-440 nm and the presence of the most important functional groups, including O-H, C-H, and C=O, which correspond to the most bioactive compounds in peel extracts used as reducing agents detected using FTIR. The antibacterial activity of produced AgNPs against S. aureus and E. coli was observed to vary with nanoparticle concentration. Higher doses of AgNPs resulted in bigger inhibition zones, with AC-AgNPs exhibiting the highest antibacterial activity compared to the other samples. The MIC values for AC-AgNPs antagonistic towards S. aureus and E. coli were 2.5 and 5 mg/mL, respectively, surpassing GM-AgNPs and MI-AgNPs.